Teenagers and the risks of sexually transmitted diseases: a need for the provision of balanced information. Issue 4 (August 1992) - Mellanby, A; Phelps, F; Lawrence, C; Tripp, J H
Abstract : OBJECTIVE--Evaluation of teenagers' knowledge and understanding about sexually transmitted disease, conception and contraception. DESIGN--A questionnaire study. SETTING--Schools SUBJECTS--1025 teenagers aged 15/16 years (mean 16.00). MAIN OUTCOME MEASURES--Scores attained in response to questions about sexually transmitted disease related to the sources of information given as most helpful. RESULTS--Teenagers have an incorrect understanding of the risks of sexually transmitted diseases. CONCLUSIONS--Teenagers may substantially underestimate their personal risk of contracting sexually transmitted diseases following the promotion of information about HIV/AIDS. Apparently simple messages about HIV and AIDS given in mass media advertising programmes may have unwanted results and need to be balanced by appropriate professional interpretation to teenagers.